Temporal Variability of Soil Reaction Among Surface and Near-Surface Horizons of Soils of Dissimilar Lithology in a Humid Tropical Environment - Onweremadu, Emmanuel; Aririguzo, Bernadine; Okoli, Nnaemeka; Afangide, Isaiah (International Journal of Environment, 2021)
The study investigated changes in soil reaction among surface and near surface horizons of four soil groups as affected by wet and dry seasons in Southeastern Nigeria. A geological map of the area guided soil sampling. Free survey approach was used in locating soil profiles. Soil samples were collected based on horizon differentiation and samples were collected from the AB-horizon (near-surface) and the A-horizon (Surface). Routine laboratory analyses were conducted on these soil samples after sieving through a 2-mm sieve. Data were subjected to analysis of variance (ANOVA) using SAS Statistical Computer Package. There were significant (p<0.05) changes in soil reaction in A- and AB-horizons in the dry seasons of 2016 and 2017. Similarly, in the wet season, soil pH varied significantly (p<0.05) in 2016 and 2017. Soil reaction significantly (p<0.05) differed in AB-horizons in both 2016 and 2017 irrespective of the season. All soil samples were acidic irrespective of lithologic material and season with pH values ranging from 4.20-5.60 and 3.31-5.42 in the A- and AB-horizons, respectively.